Enhancing Infrastructure-as-Code with Objectoriented Programming for Improving Maintainability - Nevesinjac, Miran; Tan, Qing (Proceedings of ... IEEE International Conference on Cloud Computing and Big Data Analysis (Online), 2025)
This study examines the application of ObjectOriented Programming (OOP) within Infrastructure-as-Code (IaC) frameworks that employ General-Purpose Programming Languages (GPL) to improve maintainability. By leveraging SOLID principles, it demonstrates improvements in modularity, readability, flexibility, and reduced complexity compared to traditional markup-based IaC approaches. The findings highlight benefits in code organization, reusability, and adaptability, while identifying challenges like a steep learning curve and risks of overengineering. This research provides a replicable framework for integrating OOP into GPL-based IaC, offering practical guidance for developers and paving the way for more maintainable cloud infrastructure solutions.